Inpatient Service Use by Type of Health Coverage Scheme in South Korea: A Secondary Analysis of National Data - Jeonghyun CHO; Eunmi LEE (Tehran University of Medical Sciences, 2020)
Background: Healthcare utilization has progressively increased, especially among Medical Aid (MA) beneficiaries in South Korea. Recently, the focus of MA policy is shifting to long-term inpatient management. We aimed to identify the factors associated with inpatients' medical service use among MA beneficiaries compared to National Health Insurance (NHI) beneficiaries. Methods: This secondary data analysis study used raw data collected from 2012 to 2014 by the Korea Health Panel Study, which is a national health survey conducted annually. Data from 3,869 participants were analyzed: 3,621 NHI beneficiaries and 248 MA beneficiaries. Multiple regression analysis and difference and slope difference tests were performed. Results: Age, education level, marital status, living with family, employment, disability, and unmet medical needs significantly influenced the length of hospital stay. Living with family, employment, disability, chronic illness, and unmet medical needs significantly influenced hospitalization costs. MA beneficiaries had longer hospital stay than did NHI beneficiaries (F=5.99, P=0.003); however, there was no difference in hospitalization costs. Among those with low education, longer hospital stay length was more frequent among MA beneficiaries. Conclusion: A future intervention model for MA inpatients should consider their service use patterns and characteristics. Most importantly, healthcare education should be provided according to MA patients' education level to enable patients to make informed health-related decisions. An effort is needed to change the current hospitalization system by encouraging patients to utilize local community care service and by expanding community care and in-home healthcare services.